2021
DOI: 10.1002/aisy.202100118
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Hand‐Covering Elastomeric Electronic Skin Sensor with Distributed Multifunctional Sensing Capability

Abstract: Replicating the haptic perception capability of the human hand is an indispensable goal for intelligent robots and human–machine interactions. Multifunctional electronic skin (e‐skin) sensors can be an ideal candidate to bridge the gaps among humans, robots, and the environment. Mutual interference of multistimuli and unconformable spatial distribution impedes the application of e‐skin sensors. Hence, a large‐area, hand‐covering elastomeric e‐skin sensor is proposed to imitate the human hand for multifunctiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
(68 reference statements)
0
7
0
1
Order By: Relevance
“…The addition of nano‐SiO 2 can increase Young's modulus of the bump electrode, which prevents large deformation when applied by shear force. [ 47 ] Besides, the SR/GNPs/AgNFs composite with a mass ratio of 1:0.05:0.8 has acceptable resistivity, which can provide great linearity of the measured resistance to detect shear force angle.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of nano‐SiO 2 can increase Young's modulus of the bump electrode, which prevents large deformation when applied by shear force. [ 47 ] Besides, the SR/GNPs/AgNFs composite with a mass ratio of 1:0.05:0.8 has acceptable resistivity, which can provide great linearity of the measured resistance to detect shear force angle.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical, electrical, and thermal properties of these prepared composites have been characterized in our previous work. [33] Fabrication Process of Flexible and Conformal Tactile Sensor: A fourstep procedure process was developed to fabricate the proposed flexible and conformal tactile sensor, as shown in Figure S8 (Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The maximum value is about 25% under 60 kPa. In addition, the sensor's sensing performance would also be affected by temperature, our previous work [33] indicated that the sensitivity is decreased slightly as the increasing of temperature from 20 °C to 60 °C. Compared with other flexible tactile sensors as shown in Table S1 (Supporting Information), our developed tactile sensor has relatively high sensitivities.…”
Section: Sensing Performance Characterization Of Tactile Sensormentioning
confidence: 99%
“…Topical applications of wearable strain sensors include kinematics monitoring, pose estimation, and the measurement of mechanically transduced biosignals (e.g., heart rate and speech) (1)(2)(3)(4). Soft sensor arrays have been used to map pressure and to provide feedback for soft robotics and in human interface devices (5,6). Sensing movement through textiles is unique and has potential for high impact in advancing our ability to track athletics and monitor health (7).…”
Section: Introductionmentioning
confidence: 99%